SFPE Handbook of Fire Protection Engineering - Hurley, Morgan J.; Gottuk, Daniel T.; Hall Jr., John R.; Harada, Kazunori; Kuligowski, Erica D.; Puchovsky, Milosh; Torero, Jose´ L.; Watts Jr., John M.; WIECZOREK, CHRISTOPHER J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2016)
The definitive reference on fire protection engineering, now expanded to three volumes Available in electronic format for the first time An indispensible source for reliable coverage of fundamentals, fire dynamics, hazard calculations, fire risk analysis, modeling and more SFPE members, please contact SFPE for special discount price.
Introduction to Fluid Mechanics -- Conduction of Heat in Solids -- Convection Heat Transfer -- Radiation Heat Transfer -- Thermochemistry -- Chemical Equilibrium -- Thermal Decomposition of Polymeric Materials -- Structural Mechanics -- Properties of Building Materials -- Chemical Kinetics and Fire -- Diffusion Flames -- Fundamentals of Premixed Flames -- Fire Plumes, Flame Height, and Air Entrainment -- Ceiling Jet Flows -- Vent Flows -- Effect of Combustion Conditions on Species Production -- Flammability Limits of Premixed and Diffusion Flames -- Ignition of Liquids -- Smoldering Combustion -- Spontaneous Combustion and Self-Heating -- Flaming Ignition of Solid Fuels -- Electrical Fires -- Surface Flame Spread -- Smoke Characterization and Damage Potential -- Heat Fluxes from Fires to Surfaces -- Heat Release Rates -- Calorimetry -- The Cone Calorimeter -- Compartment Fire Modeling -- Estimating Temperatures in Compartment Fires -- Zone Computer Fire Models for Enclosures -- Modeling Fires Using Computational Fluid Dynamics (CFD) -- Enclosure Smoke Filling and Fire-Generated Environmental Conditions -- Methods for Predicting Temperatures in Fire Exposed Structures -- Fire Load Density -- Combustion Characteristics of Materials and Generation of Fire Products -- Performance-Based Design -- Fire Scenarios -- Engineering Considerations for Fire Protection System Selection -- Design of Detection Systems -- Hydraulics -- Automatic Sprinkler System Calculations -- Halon Design Calculations -- Clean Agent Total Flooding Fire Extinguishing Systems -- Carbon Dioxide Systems -- Water Mist Fire Suppression Systems -- Foam Agents and AFFF System Design Considerations -- Foam System Calculations- Considerations for Coordinating and Interfacing Fire Protection and Life Safety Systems -- Smoke Control -- Smoke Management by Mechanical Exhaust or Natural Venting -- Structural Fire Engineering of Building Assemblies and Frames -- Analytical Methods for Determining Fire Resistance of Steel Members -- Analytical Methods for Determining Fire Resistance of Concrete Members -- Analytical Methods for Determining Fire Resistance of Timber Members -- Egress Concepts and Design Approaches -- Selecting Scenarios for Deterministic Fire Safety Engineering Analysis - Life Safety for Occupants -- Human Behavior in Fire -- Employing the Hydraulic Model in Assessing Emergency Movement -- Computer Evacuation Models for Buildings -- Visibility and Human Behavior in Fire Smoke -- Combustion Toxicity -- Assessment of Hazards to Occupants from Smoke, Toxic Gases, and Heat -- Engineering Data -- Liquid Fuel Fires -- Fire Hazard Calculations for Large, Open Hydrocarbon Fires -- Vapor Clouds -- Effects of Thermal Radiation to People Predicting 1st and 2nd Degree Skin Burns -- Flammable Gas and Vapor Explosions -- Dust Explosions -- BLEVEs and Fireballs -- Introduction to Fire Risk Analysis -- Probability & Statistics -- Reliability, Availability, and Maintainability -- Building Fire Risk Analysis -- Uncertainty -- Decision Analysis -- Data For Engineering Analysis -- Measuring Fire Consequences in Economic Terms -- Computer Simulation for Fire Risk Analysis -- Engineering Economics -- Fire Risk Indexing -- Risk-Informed Industrial Fire Protection Engineering -- Product Fire Risk Analysis -- Health Care Application of Quantitative Fire Risk Analysis -- The Building Envelope - Fire Spread, Construction Features and Loss Examples -- Wildland fires -- Fires in Vehicle Tunnels -- Fire Risk Assessment for Nuclear Power Plants -- Fire Risk in Mass Transportation -- Appendix A: Conversion Factors -- Appendix B: Thermophysical Property Data -- Appendix C: Fuel Properties and Combustion Data -- Appendix D: Configuration Factors -- Appendix E: Piping Properties.
Keywords: Civil engineering; Mechanical engineering; Chemicals -- Safety measures; Materials science; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Psychology, Industrial; Civil Engineering; Mechanical Engineering; Chemical Safety; Materials Science; Engineering Thermodynamics, Heat and Mass Transfer; Work and Organizational Psychology